Pe- PERAN WAWASAN NUSANTARA DALAM MENJAGA NASIONALISME GENERASI Z DI ERA GLOBALISASI DAN MEDIA SOSIAL - Syifa Rachma Permana; Fatmarani Waynia Sumaji; Siti Zulyka; Miracle Pondaag (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
ABSTRACTGlobalization and the rapid development of social media present serious challenges to Generation Znationalism in Indonesia. This study aims to examine the role of the Wawasan Nusantara as afoundation for maintaining and strengthening a sense of nationalism among Generation Z amid thedominance of social media and the tide of globalization. The method used is a systematic literaturereview with a descriptive qualitative approach, conducted through searches in Google Scholar, SINTA,Portal Garuda, and DOAJ databases covering publications from 2017 to 2025. The study’s findingsindicate that globalization and social media have both positive and negative impacts on Generation Z.On one hand, these developments open opportunities for young people to express digital nationalismthrough patriotic content and social campaigns. However, on the other hand, the unfiltered influx offoreign culture also has the potential to erode the national identity of the younger generation. WawasanNusantara has proven relevant as a national perspective capable of serving as both a filter and a guidefor Generation Z in facing these challenges. Strengthening nationalism can be achieved throughinnovation in civic education, the wise use of social media, the preservation of local culture, andparental supervision of digital media use. This study emphasizes that the values of Wawasan Nusantaramust not only be understood conceptually but also internalized in the daily lives of Generation Z.Keywords: Wawasan Nusantara, Nationalism, Generation Z, Globalization, Social Media.